Mapping Above-Ground Mangrove Ecosystems for Nature Tourism Routes to Support Sustainable Tourism Development in South Lembar Village, West Nusa Tenggara - Muhamad, Muhamad; Santosa, Djarot Heru; Kardiyati, Endah Nurhawaeny; Putra, Mohammad Alief Rizky (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
This study employed a multifaceted approach to map and quantify the above-ground carbon (AGC) content of mangrove forests using multispectral data analysis. The scoring method involved assigning values to various parameters based on their landscape characteristics. The research was conducted at beach locations in South Lembar Village and Lembar Village. Fieldwork took place in mangrove areas from July to August 2024. Sampling locations were determined using a purposive sampling method, in which samples were selected based on specific landscape criteria. The study incorporated both primary and secondary data sources. Primary data were collected through in-situ measurements and sampling, while secondary data were obtained from literature reviews and relevant institutional databases. The Random Forest (RF) classification method demonstrated high efficacy in identifying mangrove ecosystems, achieving an overall accuracy (OA) of 0.968 and a Kappa coefficient of 0.918. These metrics indicate strong agreement between the classification results and ground truth data. The analysis revealed that mangrove ecosystems covered approximately 50.08 hectares in the study area, indicating significant potential for ecotourism development, particularly for trekking routes. This study contributes to the understanding of mangrove ecosystem distribution and its potential for sustainable tourism development, particularly as climate change adaptation initiatives. The high accuracy of the mapping results provides a reliable basis for informed decision-making in environmental management and ecotourism planning. Further studies may be needed to assess the carrying capacity of these ecosystems and to develop strategies for their conservation alongside sustainable tourism practices. The mangrove area still requires overall landscape development, with assessment results showing an average score of 6.3, indicating moderate conditions and a need for improvement.